Pengembangan dan Uji Terbatas Instrumen Diagnostik Miskonsepsi pada Materi Fluida Dinamis dengan Analisis Model Rasch - Firna Agustin; Agiva Dianda Astri; Tresna Galih Sukma Suryana (Universitas Nurul Huda, 2025)
This study aims to develop and validate a diagnostic instrument based on Google Forms to identify students' misconceptions on dynamic fluid material, including the concepts of discharge, continuity equations, Bernoulli's law, and Torricelli's theorem. The research was conducted using the Research and Development (R&D) method with a 4-D development model (Define, Design, Develop, and Disseminate), but was only implemented up to the Develop stage because implementation was limited. The research subjects consisted of 35 eleventh-grade students from a Madrasah Aliyah in Serang City. The research process included instrument development, expert validation, limited testing, and data analysis using the Ministep Rasch model. The results showed that the instrument had sufficient validity and reliability, with an instrument reliability of 0.91 (good category). This instrument is effective in identifying students' misconceptions, especially regarding Bernoulli's principle. This article can contribute to the development of physics learning evaluation based on diagnostic tests.